Determination of changes in height and bone density after process preservation with synthetic bone substitute - Henao, Sandra-Lorena; Morales, Lina-Mariel; Valencia, Carlos; Arce, Sandra; Jaramillo, Adriana; Cruz, Carlos; Martínez, Carlos (Revista Estomatología, 2016)
Aim: Determine bone density and height reached fifteen (15) days and three (3) months after being grafted an sockets with a synthetic bone substitute and compared with experimental ceramic biocomposite.Materials and Methods: Thirty-seven sockets (37) selected randomly were grafted in clinics of the University of Valle, sixteen sockets (16) for control group and twenty (21) for the experimental group. CT scans were performed at 15 days and 3 months post-surgery determining bone levels: vertical height and width in the grafted area; bone density is also determined by analyzing Hounsfield units. The information obtained was processed with the STATA version 13 application frequencies for gender, type of socket and type of graft used, and for numeric variables of age, bone density, bone height, thickness crestal, averages were established and deviation were calculated standard. The confidence level was set at 95% and the significance level of 5%.Results: Bone density and height, no statistically significant differences between the intervention group (group 1) and control (group 2). For peak thickness statistically significant differences (p